Chieftaincy, the state, and democracy : political legitimacy in post-apartheid South Africa - Williams, J. Michael, 1954- (Book collections on Project MUSE., 2010)
As South Africa consolidates its democracy, chieftaincy has remained a controversial and influential institution that has adapted to recent changes. J. Michael Williams examines the chieftaincy and how it has sought to assert its power since the end of apartheid. By taking local-level politics seriously and looking closely at how chiefs negotiate the new political order, Williams takes a position between those who see the chieftaincy as an Indigenous democratic form deserving recognition and protection, a.